2014
DOI: 10.1080/19440049.2014.963699
|View full text |Cite
|
Sign up to set email alerts
|

Water availability and calcium propionate affect fungal population and aflatoxins production in broiler finisher feed during storage

Abstract: The aim of this study was to investigate the effects of calcium propionate, water activity (aw) and incubation time on the total fungal count and aflatoxins B₁ (AFB₁), B₂ (AFB₂), G₁ (AFG₁) and G₂ (AFG₂) production in the broiler finisher feed. The feed was added with calcium propionate (5 g kg(-1)), adjusted to 0.85, 0.90 and 0.95 aw and stored for 28 days at 25°C, analysing for mould growth and aflatoxins production every 7 days. Analysis of variance indicated that all the factors (preservative, aw and storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…Alam et al (2014) [30] studied the effects of calcium propionate, water activity (aw), and incubation time on the total fungal count and aflatoxins B1 (AFB1), B2 (AFB2), G1 (AFG1) and G2 (AFG2) production in broiler feed. All the factors (preservative, aw and storage time) alone and in combination significantly reduced the total fungal count and aflatoxin production in the feed.…”
Section: Acidity Regulatorsmentioning
confidence: 99%
“…Alam et al (2014) [30] studied the effects of calcium propionate, water activity (aw), and incubation time on the total fungal count and aflatoxins B1 (AFB1), B2 (AFB2), G1 (AFG1) and G2 (AFG2) production in broiler feed. All the factors (preservative, aw and storage time) alone and in combination significantly reduced the total fungal count and aflatoxin production in the feed.…”
Section: Acidity Regulatorsmentioning
confidence: 99%
“…Supporting this use, Sahib et al (2010) found that the addition of CaP could suppress the germination, growth rate, and aflatoxin production of Aspergillus flavus [1]. Similarly, a 5g/1000 g dose of CaP reduced the total fungal count and aflatoxins B1, B2, G1 and G2 production in broiler starter feed [2]. In addition, along with its use in the feed industry, CaP is also used to preserve fresh fruits and vegetables to extend the shelf life and enhance nutritional value [3].…”
Section: Introductionmentioning
confidence: 99%
“…Он содержит 21 % кальция (126). Это соединение предотвращает рост плесени и другой патогенной микрофлоры (127). Благодаря ионной связи в молекуле этой и других органических солей их растворимость выше, чем у неорганического карбоната кальция.…”
Section: взаимодействие ионов Ca 2+ с нутриентамиunclassified